Barriers to accessing treatment for pregnant women with opioid use disorder in Appalachian states. Issue 3 (3rd July 2019) - Patrick, Stephen W.; Buntin, Melinda B.; Martin, Peter R.; Scott, Theresa A.; Dupont, William; Richards, Michael; Cooper, William O.
Abstract: Background and aims : Opioid agonist therapies (OATs) are highly effective treatments for opioid use disorders (OUDs), especially for pregnant women; thus, improving access to OAT is an urgent public policy goal. Our objective was to determine if insurance and pregnancy status were barriers to obtaining access to OAT in 4 Appalachian states disproportionately impacted by the opioid epidemic. Methods: Between April and May 2017, we conducted phone surveys of OAT providers, opioid treatment programs (OTPs), and outpatient buprenorphine providers, in Kentucky, North Carolina, Tennessee, and West Virginia. Survey response rates were 59%. Logistic models for dichotomous outcomes (e.g., patient acceptance) and negative binomial models were created for count variables (e.g., wait time), overall and for pregnant women. Results: The majority of OAT providers were accepting new patients; however, providers were less likely to treat pregnant women (91% vs. 75%; p  < .01). OTPs were more likely to accept new patients than waivered buprenorphine providers (97% vs. 83%; p  = .01); rates of accepting pregnant patients were lower in both (91% and 53%; p  < .01). OTPs and buprenorphine providers accepted cash payments for services at high rates (OTP: 100%; buprenorphine: 89.4%; p  < .01); Medicaid and private insurance were accepted at lower rates. In adjusted models, providers were less likely to accept pregnant women if they took any insurance (adjusted odds ratio [aOR] = 0.15, 95% confidence interval [CI]: 0.03–0.68) or were a buprenorphine provider (aOR = 0.09, 95% CI: 0.02–0.37). Conclusions: We found that OAT providers frequently did not accept any insurance and frequently did not treat pregnant women in an area of the country disproportionately affected by the opioid epidemic. Policymakers could prioritize improvements in provider training (e.g., training of obstetricians to become buprenorphine prescribers) as a means to enhance access to pregnant women or enhancing reimbursement rates as a means of improving insurance acceptance for OAT.